Prediction of mechanical behavior of friction stir welded joints of AA3003 aluminum alloy - Ismail Chekalil; Abdelkader Miloudi; Marie-Pierre Planche; Abdelkader Ghazi (Fracture and Structural Integrity)
Friction stir welding (FSW) is an extremely complex process because it depends on the intrinsic and extrinsic factors of the material under consideration. The purpose of the present work is to formulate a set of recommendations concerning the choice of the different factors that are likely to influence the quality of the FSW joint and to find a mathematical model that allows predicting the mechanical behavior of the junction. An experimental design was therefore used to highlight the effect of the welding parameters on the behavior of the aluminum alloy  FS-Welded joint. The most influential parameters were shown to be in the order of rotational speed, feed rate and tool tilt angle. The study of the interactions between these different parameters made it possible to establish a number of combinations of the different factors for the purpose of achieving the quality optimization of the FSW joint by obtaining a tensile strength of the weld joint equal to  of that of the base metal.